The Effects of Liquid Organic Fertilizer of Vegetable Waste on The Growth of Cayenne Pepper Plants (Capsicum frutescens L.) - Baiq Elita Mandalini; Prapti Sedijani; Ahmad Raksun (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Cayenne pepper (Capsicum frustescens L.) is one of the commodities in Indonesia. The agricultural sector still relies on organic fertilizers to increase the productivity of Cayenne pepper plants. Excessive use of inorganic fertilizers will disrupt the balance of the amount of nutrients in the soil which results in plant metabolism. This study aims to determine the effect of liquid organic fertilizer from vegetable waste on the growth of cayenne pepper plants a completely randomized design (RAL) with 6 levels of treatment (0 ml, 20 ml, 40 ml, 60 ml, 70 ml and 80 ml), was used plants each with 4 repetitions and 4 fertilization times. The plant growth variables observed in this study includ plant height, number of leaves and wet weight. The data obtained were analyzed using one way Anova and further test using Duncan Multiple Range Test (DMRT) at a test level of 0.05. The results showed that the liquid organic fertilizer treatment of vegetable waste had a significant effect on the growth of cayenne pepper plants. Concentration of 80 ml of liquid organic fertilizer gave the best effect on plant height, number of leaves and wet weight among the concentrasi applied.